Cognitive Deficiency in Cannabis Consumers - Wurgan Rahadian; Abraham Sabda Respati; Supra Wimbarti; Sri Koesrohmaniah (Buletin Psikologi, 2021)
While being the most abused psychoactive substance (PS), cannabis is also the least researched PS (especially) in Indonesia. Since 24% of total PS abusers within the last year is students, we could only form an a priori on what cannabis consumption might lead to for the cognitive functions of the students. A study to explore what would happen to cognitive functions due to cannabis consumption is important. This article aims (1) to explore the effects induced by cannabis to human cognitive functions and (2) to explore which part of the brain correlated with cognitive functions affected by cannabis consumption. We conduct a literature review to answer the questions. This article shows that there is no clear conclusion whether cannabis induced positive or negative effects to human cognitive functions. It is due to various sampling technique used by the studies cited within this article. Several rationalizations stated to support our finding.